Relações públicas e gestão de marcas: compreendendo habilidades e contribuições - Rapetti, Nathália [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
This paper discusses the possible performances of professional Public Relations in Brand Management. This approach combines the concepts of brand identity, image and reputation for strategic function / managerial Public Relations. If on one hand the brand is the key element for the public identification of the organization, on the other, the result of this relationship can and should add value to both protagonists of the relationship: Public and organization. So, in an effort analytical and reflective, based on specific literature, defends the idea that the Public Relations has a professional profile that combines institutional and market interests for brand management. In practice, through an exploratory study, is observed from interviews with professionals involved in the area of Brand Management, how is the alignment between brand, relationships and purposes of the organization and which professionals working in this field. The study shows that although it is still defining itself in the market everyday, the public relations professional is a plural, able to manage this effectively

O estudo busca apresentar as possíveis atuações do profissional de Relações Públicas na Gestão de Marcas. Neste enfoque articula os conceitos de marca, identidade, imagem e reputação à função estratégica/gerencial das Relações Públicas. Se por um lado a marca é o elemento fundamental de identificação para os públicos da organização, por outro, o resultado desta relação pode e deve agregar valor a ambos protagonistas do relacionamento: públicos e organização. Por isso, num esforço analítico e reflexivo, com base em literatura específica, defende-se a ideia de que as Relações Públicas tem um perfil profissional que concilia interesses mercadológicos e institucionais para a gestão da marca. Na prática, mediante um estudo exploratório, observa-se a partir de entrevistas com profissionais vinculados à área de Gestão de Marcas, como se dá o alinhamento entre marca, relacionamentos e os propósitos da organização e quais profissionais atuam neste campo. O estudo demonstra, que embora ainda esteja se definindo no mercado cotidiano, o relaçõespúblicas é um profissional plural, capaz para fazer esta gestão com eficácia
Keywords: Gestão de negócios; Relações publicas; Imagem corporativa; Negotiorum gestio